Jurnal hubungan ilmu dengan pengetahuan : Ilmu dengan pengetahuan - Zidan, Muhammad Fatih zidan; Meyniar Albina (Cemara Education and Science, 2024)
This article tries to discuss the relationship between science, philosophy of science, and philosophy of science. The method used in this research is the Hermeneutics method with elements; interpretation and description. Philosophy, science and knowledge are basically human activities. Human activity is defined as a process as well as a result. Judging from the results, all three are the result of conscious human thinking. When viewed from the process, this third shows an activity that seeks to solve problems in human life (to obtain truth and knowledge), by using certain methods or procedures systematically and critically.